Facile synthesis of Co3O4 nanoflowers grown on Ni foam with superior electrochemical performance - Qing, Xiaoxia; Liu, Suqin; Huang, Kelong; Lv, Kezhen; Yang, Youping; Lu, Zhouguang; Fang, Dong; Liang, Xinxing (Electrochimica acta, 2011)
► Nanostructures directly grown on current-collectors displayed much higher capacitance than that of the conventional Co3O4 powders. In this paper, we report a simple solvothermal-thermal decomposition method to prepare flower-like Co3O4 grown on Ni foam. ► There have been some reports on the synthesis of one-dimensional (such as nanowires, nanotubes) and two-dimensional (such as nanoflakes) cobalt oxide on substrates. However, there are few reports on the formation of three-dimensional (3D) Co3O4 nanostructures on substrates, except the Co3O4 bowl-like nanostructures on Ni–Cu alloy film using an electrochemical method. To the best of our knowledge, there has been no report on the synthesis of Co3O4 two-dimensional nanoflower (NF) structures on substrates. In this paper, novel large-scale Co3O4 NFs on Ni foam are prepared for the first time. ► Electrochemical results show that the NFs have a high specific capacitance of 1936.7Fg−1 at a current density of 0.2Ag−1 and a capacity retention of 78.2% after 1000 cycles at a high current density of 3Ag−1 (1309.4Fg−1). Because of their ease of fabrication and optimizable performance, these NFs grown on Ni foam will hold promise in practical supercapacitors. Novel large-scale Co3O4 nanoflower (NF) structures on Ni foam are prepared for the first time via a general two-step synthesis. Through a controllable solvothermal process and hereafter with a post-calcination process in air, the NFs have been grown firmly on Ni foam, which is convenient for the construction of supercapacitors without any extra electrode preparation process. The pore sizes and the amount of Co3O4 NFs can be tuned through different post-calcination and solvothermal conditions, respectively. The electrochemical properties of the NFs are tested by cyclic voltammetry, galvanostatic charge–discharge in 6.0M KOH solution. The results show that the NFs can have a specific capacitance of 1936.7Fg−1 at a current density of 0.2Ag−1 and a capacity retention of 78.2% after 1000 cycles at a current density of 3Ag−1 (1309.4Fg−1). The Co3O4 NFs grown on Ni foam with large area and superior electrochemical performance have great potential application in supercapacitors.